Using activities-based costing in a sterile processing department as a management tool - Wellington Rodrigo de Souza; Wilza Carla Spiri; Silvana Andréa Molina Lima; Andréa Bernardes; Cláudia Helena Bronzatto Luppi (Universidade Federal de Goias, 2015)
The Center of Materials and Sterilization (CMS) is based on the cost related to the processes developed for its management and the activities-based costing (ABC) can be an adequate tool to help the manager in management decisions and practice. The aim of the study was to evaluate the application of ABC for an evidence-based management practice and its support for process of decision making. This is a case study, performed in a CMS of a teaching hospital, using documental analysis to apply the ABC. The individual cost to sterilize goods was R$ 6,05 (US$ 3,23)  and to disinfect was R$ 3,03 (US$ 1,61). The ABC is applicable and highlights evidence supporting decision making in management practice, guaranteeing the analysis of the productivity process and the decisive and impacting interventions in the management of costs.